2003
DOI: 10.1021/bi035023f
|View full text |Cite
|
Sign up to set email alerts
|

Catalase Is Regulated by Ubiquitination and Proteosomal Degradation. Role of the c-Abl and Arg Tyrosine Kinases

Abstract: Catalase is a major effector in the defense of aerobic cells against oxidative stress. Recent studies have shown that catalase activity is stimulated by the c-Abl and Arg tyrosine kinases. Little, however, is otherwise known about the mechanisms responsible for catalase regulation. The present work demonstrates that mouse cells deficient in both c-Abl and Arg exhibit increased catalase stability. The results also show that catalase is subject to ubiquitination and degradation by the 26S proteosome. Significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
58
0
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(67 citation statements)
references
References 20 publications
4
58
0
5
Order By: Relevance
“…Such a discrepancy suggests that post-translational regulation contributes to the protein levels of these antioxidant enzymes under oxidative stress conditions. Indeed, it has been reported that the protein levels of Mn SOD [21] and catalase [22] are affected by the rate of degradation via the ubiquitin-proteasome pathway in mammals. In addition, quantitative experiments such as Western blotting would be useful to determine the precise expression levels of the antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Such a discrepancy suggests that post-translational regulation contributes to the protein levels of these antioxidant enzymes under oxidative stress conditions. Indeed, it has been reported that the protein levels of Mn SOD [21] and catalase [22] are affected by the rate of degradation via the ubiquitin-proteasome pathway in mammals. In addition, quantitative experiments such as Western blotting would be useful to determine the precise expression levels of the antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, oxidative stress could cause cell death via apoptotic pathways. Several studies have shown that oxidative stress is closely associated with the proteasome, as the proteasome is involved in regulating anti-oxidants, including catalase, heme oxygenase-1 (HO-1), copper/zinc-superoxide dismutase and γ-GCS [11][12][13][14] . However, the relationship between proteasome dysfunction and oxidative stress is still a matter of dispute.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to estrogen levels, cellular redox state may also influence CAT activity. It was observed that long-term oxidative stress reduces stability and half-life of catalase by stimulating ubiquitination and proteosomal degradation of the enzyme (Cao et al 2003). However, in maintenance of cellular H 2 O 2 levels, the harmonized CAT and GPX activity is most important since H 2 O 2 plays an important role in many physiological processes like cell cycle and proliferation (Li et al 2009), regulation of enzyme activity (Ferrer-Sueta et al 2011), redox signalling (Sies 2014) and apoptosis (Andrade et al 2013).…”
Section: Discussionmentioning
confidence: 99%